Strategi Digital Marketing Funnel Dalam Mendorong Loyalitas Muzakki Pada Lembaga Zakat Dompet Dhuafa - Yuzril Mahendra; Muhamad Zen; Fatmawati (HATTA : Jurnal Pendidikan Ekonomi dan Ilmu Ekonomi, 2026)
This research is motivated by the significant gap between potential and actual zakat collection in Indonesia, necessitating an effective digital strategy to increase zakat payers' loyalty. This study aims to analyze the implementation of the 5A digital marketing funnel model (Aware, Appeal, Ask, Act, Advocate) at the Dompet Dhuafa zakat institution in building zakat payers' loyalty in the digital era. The study used a qualitative approach with descriptive-analytical methods through a literature review, the Dompet Dhuafa 2024 Annual Report, website, mobile application, social media, and various scientific journals related to digital philanthropy and digital marketing. The results show that Dompet Dhuafa has successfully integrated various digital channels such as websites, social media, mobile applications, CRM, and digital payment systems to support the zakat payers' journey from awareness to loyalty. Content strategies based on emotional, rational, and spiritual approaches have proven effective in increasing public engagement and trust. Furthermore, CRM implementation, personalized digital communications, and transparent program reports have been able to encourage loyalty and repeat donations. This study found that muzakki loyalty in the digital era is influenced by three main factors, namely trust, transparency, and ease of technology integrated into the muzakki's digital experience.